Interreligious/Interfaith Studies: Defining a New Field, edited by Eboo Patel, Jennifer Howe Peace, and Noah Silverman - Mirza, Younus Y. (Interreligious Studies and Intercultural Theology, 2019)
Interreligious/Interfaith Studies: Defining a New Field, edited by Eboo Patel, Jennifer Howe Peace, and Noah Silverman. Beacon Press, 2018. xi–xxi + 262pp. Pb., 20. 978-0-8070-1997-9